Pengembangan Modul Bahasa Inggris Berbasis ESP dengan Model ADDIE untuk Meningkatkan Kemampuan Kosakata Teknis Mahasiswa Teknik Informatika - Astuti, Fatimah Kesuma; Mulyawati, Netari (Universitas Muhammadiyah Kotabumi, 2026)
This study aims to develop an English learning module based on the English for Specific Purposes (ESP) approach that is specifically designed for Informatics Engineering students. In the field of computer science, English plays a vital role across many fields, such as technical documentation, programming, and academic resources. Accordingly, it is crucial to create learning materials that are tailored to students’ academic contexts. This research applied a Research and Development (R&D) approach by adopting the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The participants were students of Informatics Engineering at Universitas Mahakarya Asia PSDKU Baturaja. Data were collected through needs analysis questionnaires, expert validation, as well as initial test (pre-test) and final test (post-test) instruments. The results showed that the developed module was considered highly suitable according to expert evaluation and proved effective in enhancing students’ comprehension of technical vocabulary. The improvement is demonstrated by an N-Gain score of 0.54 in the moderate category, along with statistically significant results from the paired sample t-test (p < 0.05). Overall, the ESP-based module is considered effective in addressing students’ specific learning needs and enhancing their learning outcomes.